Plasmonics: Widely Adjustable and Quasi‐Reversible Electrochromic Device Based on Core–Shell Au–Ag Plasmonic Nanoparticles (Advanced Optical Materials 12/2014). Issue 12 (December 2014) - Feng, Ziying; Jiang, Chen; He, Yang; Chu, Sheng; Chu, Guang; Peng, Rufang; Li, Dongdong
<x xml:space="preserve">Abstract</x> In this article, S. Chu and co‐workers design a novel plasmonic electrochromic device. On page 1174, the reflection spectra of such a device can be actively tuned by reversibly alternating the structure of the plasmonic nanoparticle arrays. The nanoparticles are made of Au cores and Ag shells, and the thickness of the shells can be easily increased or decreased via electrochemical deposition. The sizes of these nanoparticles are controlled to ensure a blue‐to‐orange color change. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>